Assessing effectiveness in acne clinical trials: steps towards a core outcome measure set. (29th May 2019) - Thiboutot, D.M.; Layton, A.M.; Chren, M.‐M.; Eady, E.A.; Tan, J.
Summary: Background: Acne ranks second to dermatitis in terms of global burden of skin disease. As such, it is essential that data on treatment efficacy are generated in a way that maximizes the opportunity for comparison among treatments. Interest in developing core outcome sets for use in clinical trials to standardize data collection in skin disease is surging. Objectives: The goal of this review is to provide an update on the efforts underway, challenges encountered and future directions in the development of an acne core outcome measure set for use in clinical trials. Methods: The activities of the Acne Core Outcomes Research Network (ACORN) are presented in the context of currently acceptable methodologies for core outcome set development. Conclusions: Emphasis is placed on following a rigorous methodology, involving patients and recognizing a role for emerging technologies. Abstract : What's already known about this topic? In 2017, a core set of outcomes to measure in all future acne trials was proposed by the Acne Core Outcomes Research Network (ACORN) following a multistep consensus‐based process that involved patients, clinicians, trial investigators and trial sponsors from around the globe. The next step is to identify or, where necessary, develop validated instruments and standardized methods to measure each outcome in the core set. What does this study add? The processes ACORN will adopt until full validation of the core outcome measure set are described. An analysis of the main challenges in devising a core outcome measure set for international adoption is presented. Pros and cons of relying on patient‐reported outcome measures are discussed, especially in relation to global severity rating. Advances in automated acne assessment are outlined. Their relevance to the longevity of core outcome sets is highlighted. What are the clinical implications of this work? Use of a fully validated core outcome measure set, compliant with regulatory standards and universally adopted in acne clinical trials, will standardize measurement of the most important clinical outcomes and thereby facilitate pooling of data from small trials and meta‐analyses. Linked Editorial: Van Steensel. Br J Dermatol 2019; 181 :647–648 .